2021
DOI: 10.2298/pan171009012c
|View full text |Cite
|
Sign up to set email alerts
|

Endogeneity and nonlinearity in the environmental Kuznets curve: A control function approach

Abstract: This study investigates the existence and shape of an environmental Kuznets curve (EKC) across 16 developed countries and 58 developing countries during the period 1995-2010. The basic model of the EKC is a polynomial equation of real GDP per capita. The EKC model estimated for CO2 emission per capita was extended by using control variables, such as trade, urban population, fossil fuel consumption, and service sector. Based on the nonparametric test of poolability of Baltagi et al. (1996), the relationship was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 26 publications
(21 reference statements)
0
3
0
1
Order By: Relevance
“…This study performed a causality test using the approach used by Lopez & Weber (2017) and found that GDP causes environmental spending, but not the other way around. The endogeniety test, which is less problematic in a multiple regression of small variables, is performed using the method used by (Akay & Uyar, 2021). Finally, the above equations (equation 7, 8, 9, and 10) are estimated and interpreted after all panel diagnostic issues have been corrected (see appendix).…”
Section: (Eqn )mentioning
confidence: 99%
“…This study performed a causality test using the approach used by Lopez & Weber (2017) and found that GDP causes environmental spending, but not the other way around. The endogeniety test, which is less problematic in a multiple regression of small variables, is performed using the method used by (Akay & Uyar, 2021). Finally, the above equations (equation 7, 8, 9, and 10) are estimated and interpreted after all panel diagnostic issues have been corrected (see appendix).…”
Section: (Eqn )mentioning
confidence: 99%
“…This study performed a causality test using the approach submitted by Lopez & Weber (2017) and found that GDP causes environmental spending, but not the other way around. The endogeneity test is performed using the method used by (Akay & Uyar, 2021). The lack of this method was proven prior to analysis of this data set.…”
Section: (Eqn8)mentioning
confidence: 99%
“…Çağlayan Akay ve Kangallı Uyar (2019Uyar ( ), 1995Uyar ( -2010 döneminde İklim Değişikliği Konferansında belirlenen Annex II ve Non-Annex I ülke grupları için nonparametrik bir yöntem olan kontrol fonksiyonu yaklaşımı ile çevresel Kuznets eğrisi hipotezinin geçerliliğini incelenmiştir. Çalışmada kişi başına düşen karbondioksit emisyonu çevresel kirlilik göstergesi olarak kullanılmış ve açıklayıcı değişkenler kişi başına GSYH, fosil yakıt tüketimi, hizmet sektörünün ve ticaret hacminin GSYH içindeki payı ve kentleşme olarak belirlenmiştir.…”
Section: Literatürunclassified